Numerical Study of the Effect of the Penetration of a Crack in the Matrix of a Composite - Nehari, T.; Ziadi, A.; Ouinas, D.; Boutabout, B. (Engineering, Technology & Applied Science Research, 2014)
In this numerical investigation, the effect of the penetration of a crack in a matrix reinforced by aluminum silicon carbide particles in a composite is studied in order to determine the thermo-mechanical behavior under the effect of different temperature gradients during cooling. To realize this, the thermal residual stresses are calculated by considering a wide range of cracks of different penetrations. The results of this investigation compared to a case without geometric discontinuity, have revealed no meaningful effect of the distribution of the stresses along a main direction perpendicular to the direction of the crack. On the other hand, regarding the distribution of the stresses along the plane of the crack and in vicinity of the particle, results show that the penetration of the crack in the matrix causes an asymmetry.